2015
DOI: 10.3390/ijms161025881
|View full text |Cite
|
Sign up to set email alerts
|

Heat Killed Lactobacillus reuteri GMNL-263 Reduces Fibrosis Effects on the Liver and Heart in High Fat Diet-Hamsters via TGF-β Suppression

Abstract: Obesity is one of the major risk factors for nonalcoholic fatty liver disease (NAFLD), and NAFLD is highly associated with an increased risk of cardiovascular disease (CVD). Scholars have suggested that certain probiotics may significantly impact cardiovascular health, particularly certain Lactobacillus species, such as Lactobacillus reuteri GMNL-263 (Lr263) probiotics, which have been shown to reduce obesity and arteriosclerosis in vivo. In the present study, we examined the potential of heat-killed bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…In other studies, heat-killed non-viable forms of L. reuteri GMNL-263 were potent enough to prevent weight gain in a diet-induced obesity rat model (Hsieh et al, 2016). In high-fat diet fed hamsters, the same heat- treated material reduced liver fibrosis, blood LDL-cholesterol and plasma malondialdehyde and myocardial cell apoptosis (Ting et al, 2015a,b). A heat-killed L. reuteri ATCC 23272 also reduced pro-inflammatory cytokines, but was less potent than viable forms in reducing eosinophil influx and airway damage (Forsythe et al, 2007); however, killed bacteria were able to reduce visceral pain (Kamiya et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…In other studies, heat-killed non-viable forms of L. reuteri GMNL-263 were potent enough to prevent weight gain in a diet-induced obesity rat model (Hsieh et al, 2016). In high-fat diet fed hamsters, the same heat- treated material reduced liver fibrosis, blood LDL-cholesterol and plasma malondialdehyde and myocardial cell apoptosis (Ting et al, 2015a,b). A heat-killed L. reuteri ATCC 23272 also reduced pro-inflammatory cytokines, but was less potent than viable forms in reducing eosinophil influx and airway damage (Forsythe et al, 2007); however, killed bacteria were able to reduce visceral pain (Kamiya et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies have shown that Oscillospira genus appears to be reduced in patients with NAFLD and NASH . Further, several clinical trials have shown an improved disease state associated to the treatment with different species of Lactobacillus genus as a probiotic . The relative abundance of these genera in dHFD− , in addition to its specific profile at phylum and class levels, could be related to a protective functionality against NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mice fed methionine-choline diet, a model of severe NASH not associated with obesity or the metabolic syndrome, developed less liver fibrosis when treated with VSL#3 [ 130 ]. Other probiotics also showed beneficial effects in animal models of NAFLD/NASH [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ].…”
Section: Microbiota As a Therapeutic Targetmentioning
confidence: 99%